Hepatitis A virus vaccination strategy and pre-immunization screening of Bangladeshi children - Mahmud, Salahuddin; Karim, ASM Bazlul; Alam, Jahangir; Islam, MM Ziaul; Sarker, NK; Munshi, AS; Sarker, Shaoli (Bangladesh Journal of Medical Science, 2015)
Background: HAV infection is endemic in many developing countries like India, Pakistan, Nepal etc. Several seroprevalence studies show high rates of sero-positivity among children by sub-clinical infection. Therefore mass vaccination against HAV has not been recommended in endemic countries. Objective: To determine whether routine hepatitis A vaccination is indicated for all Bangladeshi children & also to know whether pre-vaccination screening is necessary. Materials & Methods: Serum samples from 254 children aged between 1-15 years were tested for antibody (IgM & IgG) against hepatitis A virus (HAV) to determine the seroprevalence of HAV antibody and do a cost-benefit analysis for decision making about vaccination against HAV among the children of Bangladesh. Results: Hepatitis A virus antibody was positive in 141 (55.5%) of 254 children. Age-specific sero-prevalence was 13 (23.2%) of 56 in 1-3 year, 64 (55.2%) of 116 in 3-5 year, 39 (70.9%) of 55 in 5-10 year & 25 (92.6%) of 27 in 10-15 year age group. Cost benefit analysis showed that the total cost of screening followed by vaccination was almost 1.8 times less than the total cost of vaccination of all children without screening. Conclusions: Majority of the children were found sero-positive against HAV around 15 year of age. Therefore mass vaccination against HAV may not be required for Bangladeshi children. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21561 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.65-69